Environmental education, competition and creativity in the training of biology teachers - Miranda López, Aurora del Carmen; Guerra Salcedo, Marisela de la Caridad; Colunga Santos, Silvia (Transformación, 2024)
Objective: This paper explains the theoretical conception involved in the development  a creative competence for environmental education by biology teachers’ trainees giving emphasis to its framework.Methods: The authoresses rely on analytic-synthetic, inductive-deductive methods, as well as on the systemic and the functional structural systemic approaches to construct the theoretical framework and to devise the systematic conception mentioned above.Result: The finding is a description of the process of the teacher trainees’ environmental education creative competence. This process is fostered by connecting creativity to environmental education, arising an innovating atmosphere, and stimulating personal resources. Conclusion: The development of the creative competence for environmental education is possible on the basis of a systematic conception connecting the comprehension of the environmental creative context, a creative approach to environmental education and the innovative environmental transformation.
Keywords: teacher education; environmental education; creative teaching; creative ability.